The responsibility to defend rethinking Germany's strategic culture - Giegerich, Bastian 1976-; Terhalle, Maximilian 1974- (Adelphi (Series) (International Institute for Strategic Studies), 2021)
"The rise or resurgence of revisionist, repressive and authoritarian powers threatens the Western, US-led international order upon which Germany's post-war security and prosperity were founded. With Washington increasingly focused on China's rise in Asia, Europe must be able to defend itself against Russia, and will depend upon German military capabilities to do so. Years of neglect and structural underfunding, however, have hollowed out Germany's armed forces. Much of the political leadership in Berlin has not yet adjusted to new realities or appreciated the urgency with which it needs to do so." -- Publisher website.